2015
DOI: 10.1038/nmat4479
|View full text |Cite
|
Sign up to set email alerts
|

A new active Li–Mn–O compound for high energy density Li-ion batteries

Abstract: The search for new materials that could improve the energy density of Li-ion batteries is one of today's most challenging issues. Many families of transition metal oxides as well as transition metal polyanionic frameworks have been proposed during the past twenty years. Among them, manganese oxides, such as the LiMn2O4 spinel or the overlithiated oxide Li[Li1/3Mn2/3]O2, have been intensively studied owing to the low toxicity of manganese-based materials and the high redox potential of the Mn(3+)/Mn(4+) couple.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
247
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(261 citation statements)
references
References 29 publications
13
247
0
1
Order By: Relevance
“…The Li-Mn-O system is promising for the further enhancement of the specific capacity of the cathode material and, hence, the energy density of the Li-ion cells. Recently, a Li-Mn-O system of nominal composition, "Li 4 Mn 2 O 5 ", was reported as a novel cathode material with a specific capacity exceeding 300 mA·h/g by an Mn 3+ /Mn 5+ two-electron redox process, as was confirmed by magnetic measurements [43]. The oxide is prepared by a mechano-chemical route at ambient temperature using orthorhombic LiMnO 2 and Li 2 O with a 2:1 molar ratio.…”
Section: Introductionmentioning
confidence: 87%
“…The Li-Mn-O system is promising for the further enhancement of the specific capacity of the cathode material and, hence, the energy density of the Li-ion cells. Recently, a Li-Mn-O system of nominal composition, "Li 4 Mn 2 O 5 ", was reported as a novel cathode material with a specific capacity exceeding 300 mA·h/g by an Mn 3+ /Mn 5+ two-electron redox process, as was confirmed by magnetic measurements [43]. The oxide is prepared by a mechano-chemical route at ambient temperature using orthorhombic LiMnO 2 and Li 2 O with a 2:1 molar ratio.…”
Section: Introductionmentioning
confidence: 87%
“…66 Recently, Li 4 Mn 2 O 5 with the partial anion redox has been published. 67 A new system with Li 2 O-based materials has been also proposed in the literature.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…As mentioned earlier, the pristine cathode materials suffer from structural degradation in long-term cycling in LIBs at elevated temperatures and under high current operation. [45][46][47][48] Therefore, the efficient usage of oxygen atoms for prolonging the safety life of cathode materials and promoting high energy density could be a potential future research challenge. An early study by Dahn and co-workers investigated the influence of simple heattreatment of LCO on its electrochemical performance at 4.5 V vs Li and concluded that the poor performance of the battery was possibly associated with unwanted side reactions of LCO with the electrolyte and that its electrochemical properties were improved without the necessity for any surface coating with foreign materials.…”
Section: Lithium-ion Batteriesmentioning
confidence: 99%